Brain state expression and transitions are related to complex executive cognition in normative neurodevelopment - Medaglia, John D.; Satterthwaite, Theodore D.; Kelkar, Apoorva; Ciric, Rastko; Moore, Tyler M.; Ruparel, Kosha; Gur, Ruben C.; Gur, Raquel E.; Bassett, Danielle S. (NeuroImage (Orlando, Fla.), 2018)
Adolescence is marked by rapid development of executive function. Mounting evidence suggests that executive function in adults may be driven by dynamic control of neurophysiological processes. Yet, how these dynamics evolve over adolescence and contribute to cognitive development is unknown. In a sample of 780 youth aged 8–22 yr (42.7% male) from the Philadelphia Neurodevelopment Cohort, we use a dynamic graph approach to extract activation states in BOLD fMRI data from 264 brain regions. We construct a graph in which each observation in time is a node and the similarity in brain states at two different times is an edge. Using this graphical approach, we identify two primary brain states reminiscent of intrinsic and task-evoked systems. We show that time spent in these two states is higher in older adolescents, as is the flexibility with which the brain switches between them. Increasing time spent in primary states and flexibility among states relates to increases in a complex executive accuracy factor score over adolescence. Flexibility is more positively associated with accuracy toward early adulthood. These findings suggest that brain state dynamics are associated with complex executive function across a critical period of adolescence. •We uncover two primary brain states in 780 subjects from 8yr to 22yr of age.•Primary states correspond to “Task-Positive” and “Task-Negative” networks.•Greater time spent in primary states is associated with better executive function.•Flexibility is differentially linked to executive function in younger/older youth.•State-level analysis identifies behaviorally relevant features of neurodevelopment.